BORROWING WORD ANALYSIS IN "I FINE THANK YOU LOVE" MOVIE - Nur Fitria, Tira (Lire Journal (Journal of Linguistics and Literature), 2019)
The objectives of this research are to describe the types of borrowing word and to find out the dominant type of borrowing words found in “I Fine Thank You Love You” movie. This research is descriptive qualitative research. Descriptive research tries to present the problem clearly based on the accurate data, explaining and describing the topic of a problem based on the theory used. From the analysis, it is found that there are two types of borrowing word found in “I Fine Thank You Love You” movie, they are pure and naturalized borrowing. In pure borrowing, there are 43 data or 38.39 %. While, in naturalized borrowing, there are 69 data or 61.61 %. It shows that pure borrowing shows high percentage than naturalized borrowing. In pure borrowing, a word purely taken from the source language (SL) into the target language (TL) without changing any letters. While, in naturalized borrowing, a word can be naturalized to fit the spelling rules in the target language (TL) so the readers can understand easily what the word means